2011
DOI: 10.1016/j.jmii.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen worsens Streptococcus pyogenes soft tissue infections in mice

Abstract: The results supported the concept that ibuprofen use in GAS soft tissue infections might induce the development of severe necrotizing infections and increase mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 17 publications
4
29
1
10
Order By: Relevance
“…Even so, other animal studies confirmed the role of NSAIDs in aggravating cellular tissue infection [14].…”
Section: Discussionmentioning
confidence: 94%
“…Even so, other animal studies confirmed the role of NSAIDs in aggravating cellular tissue infection [14].…”
Section: Discussionmentioning
confidence: 94%
“…The animal models fail to fully reproduce the anatomic and bacteriological conditions found as CFC risk factors in humans. Even so, other animal studies confirmed the role of NSAIDs in aggravating cellular tissue infection [13].…”
Section: Discussionmentioning
confidence: 94%
“…All of the pipettings in the assay were performed by Biotek Precision robotic system (BioTek Instruments, Inc., Winooski, VT). Fluorescence (Ex/Em ¼535/587 nm) of the samples were kinetically measured by BioTek-Synergy H1 multimode microplate reader (BioTek Instruments, Inc., Winooski, VT) at 25 C for 5-10 min. Appropriate two points (T1 and T2) in the linear range of the plot were chosen, and the corresponding fluorescence values (RFU1 and RFU2) were obtained.…”
Section: Cox-1 and Cox-2 Inhibition Assaymentioning
confidence: 99%
“…Additionally, inflammation may cause accumulation of fluid in the injured area, which may stimulate bacterial growth 24 . Other reports revealed that NSAIDs may increase the progression of bacterial infection 25,26 . Furthermore, in the management of infectious and inflammatory diseases, the use of multidrug therapy is an increasing concern for patients with damaged liver or kidney functions, patients with diseases of the gastrointestinal system or patients suffering from diverse side effects of other drugs.…”
Section: Introductionmentioning
confidence: 98%